ОРГАНІЗАЦІЯ АМБУЛАТОРНО-ПОЛІКЛІНІЧНОГО ОБСЛУГОВУВАННЯ НАСЕЛЕННЯ В УКРАЇНІ: ІСТОРИЧНИЙ ПОГЛЯД - Tarallo, Volodymyr; Vatsyk, Mariya (Aktualʹnì pitannâ suspìlʹnih nauk ta ìstorìï medicini (Online), 2018)
Any transformation in the healthcare system should improve the quality and accessibility of health services for all segments of the population. The authors tried to observe only the leading historical recreational activities that have contributed to such changes during many years of development of outpatient clinics in Ukraine. The purpose of the study is to give an overview of the leading organizational and recreational activities, which implementation in the health care of Ukraine was contributed to improving the quality and accessibility of health services in the primary sector of the industry. Materials and methods. The system-historical analytical method was used for the bibliography processing of the medicine in Ukraine development during the 1920-2018. Scientific novelty. The article presents the leading organizational and recreational activities carried out in the health care of Ukraine for 100 years with the aim of creating high-quality and affordable outpatient and polyclinic care for all sexually-populated groups of the population in cities and rural areas, taking into account the structural features of industrial employment of persons work in the national economy, and the milestones of critical periods in the life of the country and its inhabitants. Positive experience and inadequate programs (as well as individual measures) are presented to improve primary health care. Their focus on prophylactic components of medical care with the implementation of the principles of economization, humanization and gradual cybernetization, preserving the best traditions of Ukrainian medical care, timely detection of diseases, reducing the overall morbidity and mortality, the inadmissibility of epidemics, a significant increase in life expectancy against the background of the gradual implementation of the principles of affordable and highly skilled family medicine. Conclusions. The history of the establishment of the ambulatory and polyclinic service in the health care of Ukraine laid the general and targeted social, economic, ecological, and organizational directions of the development of pre-medical, medical and preventive medicine in Ukraine. The restructuring of the created service in order to comply with artificial "world standards" without taking into account many years of national, territorial, ethnic and social traditions does not provide certainty in the future about improving the social conditions, accessibility and quality of traditional medical services.